Unveiling Tomorrow’s Labor Market: A Data-Driven Forecast of Open Unemployment in Bandung Regency (2025–2029) - Simamora, Daniel (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to project the Open Unemployment Rate (OUR) in Bandung Regency for the 2025–2029 period. Unemployment is a crucial issue that reflects economic health and social welfare, making accurate forecasting a vital instrument for regional development planning. Utilizing annual time-series data of OUR from the Central Statistics Agency (BPS) for the period 2007–2024, this research applies the Box-Jenkins methodology through the Autoregressive Integrated Moving Average (ARIMA) model. The analysis process includes stationarity tests, model identification, parameter estimation, and diagnostic checking. The model selection results, based on the lowest Akaike Information Criterion (AIC) and Bayesian Information Criterion (BIC), indicate that ARIMA(0,1,1) is the most parsimonious model. The resulting projection indicates a very significant downward trend in the OUR, from 6.36% in 2024 to 3.21% in 2029. Although this projection is highly optimistic, the volatility of the historical data and the univariate nature of this model imply that the realization of this trend is highly dependent on economic stability and the effectiveness of sustained policies to address structural employment issues. Keywords: Forecasting, Unemployment, ARIMA, Bandung Regency